TMIC-55. IMMUNE DIGITAL-SPATIAL PROFILING AND CHARACTERIZATION OF GLIOMA MICROENVIRONMENT AFTER ADOPTIVE CELLULAR THERAPY. (14th November 2022) - Font, Laura Falceto; Jin, Dan; Dean, Bayli DiVita; Francis, Connor; Reid, Alexandra; Sebastian, Mathew; Figg, John; Long-James, Kaytora; Deleyrolle, Loic; Flores, Catherine
Abstract: INTRODUCTION: Our group has previously shown that Adoptive Cellular Therapy (ACT) is efficacious against CNS malignancies including medulloblastoma, brain stem glioma, and glioblastoma. In this study, we characterized the spatial distribution of immune cells within the tumor microenvironment after ACT and conducted regional genomic analysis in situ to obtain insights into the underlying cellular dynamics. This method enabled us to define specific differences in gene expression within the T cells in the treated versus untreated tumors including changes in gene expression of regulatory T cell (Treg) associated genes, such as Runx1 and TGF-β. We also found a significant increase in Batf3 expression associated with therapy. METHODS: We performed in situ GeoMx Digital Spatial Profiling (DSP) and whole genome transcriptomics (RNA) of murine glioma KR-158B-luciferase tumors after adoptive cellular therapy. ACT was conducted in orthotopic KR158B tumor-bearing mice. Histological slides were sent to be stained for CD45, CD3, GFP (to mark hematopoietic stem cell-derived cells) and nuclei, and processed following GeoMx DSP workflow for RNA. Overall gene expression clustering profiles were conducted using a Principal Component Analysis (PCA), and relative gene expression differences were analyzed by unpaired t-tests. RESULTS/CONCLUSIONS: We observed differential expression of a substantial number of genes in the ACT-treated group compared to control. Our findings also indicate that tumors treated with ACT cluster separately from control tumors in PCA analysis. Furthermore, we found downregulation of genes associated with the suppressive properties of regulatory T cells (Runx1 and TGF-β), and upregulation of dendritic cell characteristic genes (Batf3) and antigen presentation genes (H2-Ab1) in ACT-treated tumors vs control. These findings provide insights into the immune cell dynamics and specific genes that are differentially expressed within the tumor microenvironment. This could help improve current adoptive cellular therapies to treat brain tumors.